An Analysis of Subject-Auxiliary Inversion Errors in EFL Students' Writing - Tarigan, Najwa Ramadhani; Luthfi, Jihan; Purnama, Dirza Rizki; Ismahani, Siti (Perkumpulan Manajer Pendidikan Islam Indonesia (PERMAPENDIS) Prov. Sumatera Utara, 2025)
In English as a Foreign Language (EFL) writing, grammar is essential for achieving precision and clarity, particularly when it comes to creating questions. The subject and auxiliary verb must be reversed in yes/no and wh-questions, according to the necessary grammatical form known as subject-auxiliary inversion (SAI). Using a descriptive quantitative methodology, this study seeks to analyze the frequency and patterns of SAI mistakes in the writing of EFL learners. Twenty-two undergraduate EFL students from the State Islamic University of North Sumatra (UINSU) from various academic semesters made up the participants. Using a structured grammar test modified from Azar (2009) and administered electronically using Google Forms, data were collected. The frequency and kinds of inversion mistakes were determined using descriptive statistics and error analysis in the analysis. The results demonstrate that SAI is utilized with a very high overall accuracy rate (over 95%), suggesting that the majority of students have fully absorbed this grammatical principle. Nevertheless, there were still some little mistakes, especially in statements using present simple, past simple, and present perfect auxiliary verbs. Although formal grammar teaching is generally successful, these findings indicate that there is still a need for focused reinforcement on tense-auxiliary alignment. By highlighting the significance of targeted remedial grammar exercises in improving grammatical precision in writing, the research offers practical pedagogical recommendations for EFL teaching.